1992
DOI: 10.1346/ccmn.1992.0400306
|View full text |Cite
|
Sign up to set email alerts
|

Electroacoustic Study of Adsorption of Cetylpyridinium Chloride on Kaolinite

Abstract: Abstract--Adsorption of cetylpyridinium chloride (CPC) onto kaolinite can be followed using the electroacoustic effect. The dynamic mobility, measured at a frequency of l MHz, varies from about -2 to +I x 10 s m E V-i s-J in a number of steps, reflecting the adsorption of two separate layers, with the bilayer being more obvious, especially at pH 5-8. The behaviour at different pHs reflects the different charge characteristics of the basal cleavage planes and the crystal edges. When the amount of added CPC is e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 11 publications
(6 reference statements)
0
2
0
Order By: Relevance
“…BET measurements gave a figure of 18 m2/g and an electroacoustic study of CP + adsorption by Rowlands and Hunter (1992) gave 21 m2/g, which seems to be a more reliable figure. Figure 1 shows the behavior of the quartz suspension alone and in the presence of two concentrations of added Co 2+ ion.…”
Section: Resultsmentioning
confidence: 87%
“…BET measurements gave a figure of 18 m2/g and an electroacoustic study of CP + adsorption by Rowlands and Hunter (1992) gave 21 m2/g, which seems to be a more reliable figure. Figure 1 shows the behavior of the quartz suspension alone and in the presence of two concentrations of added Co 2+ ion.…”
Section: Resultsmentioning
confidence: 87%
“…While other studies have demonstrated that purified soil constituents can adsorb and potentially affect the subsequent degradation of chemicals, most of these studies have not been performed under typical soil solution conditions with intact soil communities. Commonly, the adsorption and desorption of chemicals is examined in dilute solutions of the soil constituent, which do not represent the typical soil solutions or soil water activity (a,) (6,12,31,38,39,41). The unique value of this study is that mineralization of chemicals in known environmental forms was measured under realistic aw conditions, at which the biological, chemical, and physical characteristics of a natural soil were largely preserved.…”
Section: Discussionmentioning
confidence: 99%